Role of Micro, Small and Medium Enterprises (MSMEs) In the Development of India's Women Entrepreneurship (International Journal of Innovative Research in Engineering & Management, 2022)
Women entrepreneurs play a critical role  in the globalised world, and they have becomeing an  indispensable component of the worldwide search for  sustainable financial growth and social progress.  Women's entrepreneurship is a comparatively new  phenomena. Women-owned businesses are rapidly  developing in practically all economies as a result of  increased industrialization, social laws, urbanisation,  political and economic developments. Women's roles  have evolved from the kitchen to higher levels of  professional activity as a result of increased education  and awareness. In India, women's entrepreneurship is  gaining traction. Women are increasingly becoming  entrepreneurs in modern India, particularly in MSMEs.  Women entrepreneurs, on the other hand, confront a slew  of societal, economic, and familial issues. This article  focuses on the challenges that women entrepreneurs  confront in today's competitive business climate.
Keywords: Entrepreneurship; MSMEs; Sustainable Economic Development; Women Entrepreneurship